EXPERT SYSTEM FOR INITIAL IDENTIFICATION OF DISEASES CAUSED BY HELICOBACTER PYLORI BACTERIA USING CASE BASED REASONING APPROACH - Dasril Aldo (Informatika, Universitas Jenderal Soedirman, 2023)
Helicobacter pylori, which is a bacterium that can live in the stomach. Infection can occur when bacteria invade and damage the stomach wall. Lack of information and ignorance of the public about the seriousness of these bacteria causes various very serious diseases such as inflammation of the digestive tract (gastritis), gastric bleeding, gastric perforation (leak stomach), infection of the peritoneal wall (peritonitis) and gastric cancer. This expert system aims to provide information and also early identification of diseases caused by the bacterium Helicobacter pylori. After the expert system has identified the type of disease, it will then suggest the actions that need to be taken. The method used is CBR, this method works with the stages of Retrieve, Reuse, Revise, and Retain. The data that will be processed in this study are 30 data, with the results of 29 data in accordance with the doctor's diagnosis. From these results, it can be said that the accuracy of this expert system is 97% so that it can be used as an alternative in identifying diseases caused by the bacterium Helicobacter pylori.